2020
DOI: 10.1002/essoar.10504785.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Needle Propagation and Twinkling Characteristics

Abstract: Needles are a very recently discovered lightning phenomenon, described in Hare et al. (2019), that occur along positive leader channels. They appear like small leader branches, at most around 100-m long, and stick out from the channel. However, unlike leader branches, they exhibit ionization fronts that propagate up each needle, away from the positive leader channel. Hare et al. (2019) referred to these fronts as twinkles, and they occur at a very regular rate, around once per 5 ms. Pu and Cummer (2019) confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…This is different from the pulsating repetition of the needle extension from the surface of hot channel core that was hypothesized by Hare et al. (2019, 2021), Pu and Cummer (2019), and Saba et al. (2020).…”
Section: Discussion and Summarymentioning
confidence: 58%
See 3 more Smart Citations
“…This is different from the pulsating repetition of the needle extension from the surface of hot channel core that was hypothesized by Hare et al. (2019, 2021), Pu and Cummer (2019), and Saba et al. (2020).…”
Section: Discussion and Summarymentioning
confidence: 58%
“…Hare et al. (2021) showed detailed characteristics of needle propagation and flickering and observed that recoil leaders quench needle activity. Saba et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the notable asymmetries is that the positive leader could reactivate in the form of recoil leader after cooling down or being cutoff, while the negative leader rarely does (Mazur, 2002, 2016; Qie et al., 2017). Lightning positive leader propagation draws more attentions these years, and new insights into its physical characteristics and mechanism are revealed with data in different aspects obtained by comprehensive observations (R. Jiang et al., 2020; Hare et al., 2021; Visacro et al., 2017; Zhao et al., 2021). Yuan et al.…”
Section: Introductionmentioning
confidence: 99%